AMMONIUM IN GRANITES AND ITS PETROGENETIC SIGNIFICANCE - Hall A. (My University, 1998)
Ammonium is present as a trace constituent in all granites, with an average concentration of 45 ppm (NH4+), equivalent to 35 ppm of elemental N. It shows wide variations related to petrography and region, but the only significant correlation between ammonium and other geochemical parameters is that it is most abundant in peraluminous granites and least abundant in peralkaline granites. These variations can be related to (a) the amount of sedimentary material in the magmatic source region, and (b) redox conditions in the source region. The ammonium content of granitic magmas can also be modified by fractionation or contamination. Hydrothermal alteration has a major effect on the ammonium content of granitic rocks, and variation due to this cause may exceed the magmatic variation. Most hydrothermally altered granites are enriched in ammonium as a result of the transfer of ammonium from sedimentary country rocks by the hydrothermal fluids